Analisis Pengaruh Laju Aliran Massa Dan Radius Fillet Terhadap Perubahan Tekanan Pada Venturi Meter Menggunakan Simulasi CFD - Satria Wahyu Wibowo Putra; Oleh Oleh; Aa Santosa (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to protect copyright and the government's Venturi meter is a tool for measuring the mass flow rate or volume flow in a closed channel. The geometry and dimensions of the Venturi meter consist of various shapes, especially on the neck which is used as a barrier. The shape of the Venturi meter that is widely used varies, but basically has the same way of working, namely by measuring the pressure difference at two specified points. Dimensional changes between the slope and the neck of the venture can cause differences in pressure values. The two points set are the highest points for the pressure difference that occurs on the measuring instrument. Calculations only involve the equations of Energy, pressure and flow continuity. From the analysis of the change in the average pressure accurately occurred at a tap distance of L = 125 mm and an average pressure at 674.6 Pa for flow rates of 0.2 and 0.5 kg/s with fillet sizes between 45 – 50 mm.